Pengelolaan Barang Milik Negara di Kantor Bappeda Litbang Kabupaten Bone Bolango - Hola, Miftahulzana; Mozin, Sri Yulianty; Abdussamad, Juriko (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This study aims to determine, describe, and analyze the management of State Property at the Bappeda Litbang Office of Bone Bolango Regency. The approach used in this research is qualitative. The research method is descriptive qualitative. Data collection was carried out using interview techniques, observation, and documentation studies. Data analysis techniques in this study were carried out by data reduction, data presentation and conclusion drawing/verification. The results of the study that in the planning aspect, the preparation of the Regional Property Needs Plan (RKBMD) is carried out annually with procurement based on operational needs. In the implementation and utilisation aspects, some elements of BMN procurement and utilisation have run effectively. In the aspect of supervision, it has involved various internal, external, and community parties. However, there are still several obstacles in BMN management at the Bone Bolango Regency Bappeda Litbang Office, such as data that has not been integrated. Suggestions to optimise the management of State Property at the Bone Bolango Regency Bappeda Litbang Office require technology development to improve data integration through effective information systems, coordination, and transparency.